2012
DOI: 10.1002/jor.22289
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis, senescence, and autophagy in rat nucleus pulposus cells: Implications for diabetic intervertebral disc degeneration

Abstract: This research was aimed to study the mechanisms by which diabetes aggravates intervertebral disc degeneration (IDD) and to discuss the relationship between autophagy and IDD in nucleus pulposus (NP) cells. Sixteen weeks after injecting streptozotocin (STZ), the intervertebral discs (IVDs) were studied by histology, Alcian blue, 1,9-dimethylmethylene blue (DMMB), immunohistochemistry, and RT-PCR to explore the IDD. The apoptosis and senescence of NP cells was investigated by terminal deoxyribonucleotidyl tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
145
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(150 citation statements)
references
References 64 publications
5
145
0
Order By: Relevance
“…The result of this research is consistent with our previous study, which indicated that autophagy was increased in rats with type I diabetes mellitus [2]. Generally, the appropriate increase of autophagy in the chondrocyte and annulus fibrosus cells is considered to be an adaptive reaction to different types of stresses and play a protective role maintaining the homeostasis within cells.…”
supporting
confidence: 92%
“…The result of this research is consistent with our previous study, which indicated that autophagy was increased in rats with type I diabetes mellitus [2]. Generally, the appropriate increase of autophagy in the chondrocyte and annulus fibrosus cells is considered to be an adaptive reaction to different types of stresses and play a protective role maintaining the homeostasis within cells.…”
supporting
confidence: 92%
“…76,77 An altered level of autophagy during intervertebral disc degeneration and aging has been reported. [37][38][39][40]78 Our studies clearly show evidence of MTOR-independent, noncanonical autophagy in NP cells. In addition, hypoxic induction of autophagy is independent of HIF1 as well as increased oxidative stress.…”
Section: Discussionsupporting
confidence: 57%
“…1,33,36 Not surprisingly, changes in autophagy have also been associated with disc degeneration. Although the causative relationship between disc degeneration and autophagy is not yet clear, alterations in the level of autophagy have been observed in degenerated IVDs, IVDs of aged or diabetic rats [37][38][39] and NP cells derived from degenerative human discs. 40 In addition, various stresses such as high glucose, 41,42 aberrant mechanical compression, 43 lactate overload, 44 glucosamine, 45 and reactive oxygen species (ROS), 43 activate autophagy in NP cells, further implicating autophagy modulation as a possible contributor to disc pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…The role of apoptosis and apoptosis-related genes in the development of degenerative diseases has garnered much attention in recent years. The excessive apoptosis of NP cells, which are capable of producing ECM components, is one of the most discernable cellular and biochemical changes credited to degeneration (17)(18)(19)(20)(21)(22). A previous study demonstrated that NP cells predominantly undergo apoptosis via the death receptor pathway, which contributes to degeneration of the intervertebral disc (23).…”
Section: Discussionmentioning
confidence: 99%